MEDIA SOSIAL DAN PERCERAIAN: IMPLIKASI, STRATEGI PENCEGAHAN SERTA PERAN PENDIDIKAN PRANIKAH - Susan Agustina Putri; Mirna Nur Alia Abdullah (Yayasan Literasi Sains Indonesia, 2025)
Divorce is a social phenomenon that is not uncommon in society, divorce also causes the breakup of a couple’s relationship that was previously bound by marriage vows, causing a change in the status that a person has in society. Divorce has a significant effect in contributing to the source of social problems in society if the crisis that occurs in this divorce is not resolved properly. The purpose of this research is to know the indications of divorce, especially those caused by the implications of misuse of social media unwisely, and to understand the right steps in dealing with the risk of divorce by strengthening premarital education. The research method used is a literature study with the technique of analyzing, identifying and exploring secondary data from research in the form of articles or journals that have existed before to be closely related to the topic under study. The results show various factors that trigger the failure and success of marriage in the household along with solutions that can be applied by elaborating functional structural theory through premarital education programs.